2018
DOI: 10.1186/s13068-018-1247-0
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of South African sugarcane bagasse using a low-cost protic ionic liquid: a comparison of whole, depithed, fibrous and pith bagasse fractions

Abstract: BackgroundSugarcane bagasse is an abundant and geographically widespread agro-industrial residue with high carbohydrate content, making it a strong candidate feedstock for the bio-based economy. This study examines the use of the low-cost protic ionic liquid triethylammonium hydrogen sulfate ([TEA][HSO4]) to fractionate a range of South African sugarcane bagasse preparations into a cellulose-rich pulp and lignin. The study seeks to optimize pretreatment conditions and examine the necessity of applying a depith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 56 publications
3
38
0
1
Order By: Relevance
“…The higher residual lignin content is likely an obstacle to achieving higher saccharification yield from the pulps, expecially for pine. While it has been shown that pine delignification by ionosolv solutions can be enhanced by applying temperatures above 150 °C and using different cations, the change in conditions may negatively affect FA‐yield and selectivity as shown for beech and an increased reaction temperature (Table ). Although the cellulose content was increased compared to untreated biomass (41 %), it is low if the target is material applications (>80 %, with the lignin content being as low as possible), hence improved delignification is a target for further optimisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher residual lignin content is likely an obstacle to achieving higher saccharification yield from the pulps, expecially for pine. While it has been shown that pine delignification by ionosolv solutions can be enhanced by applying temperatures above 150 °C and using different cations, the change in conditions may negatively affect FA‐yield and selectivity as shown for beech and an increased reaction temperature (Table ). Although the cellulose content was increased compared to untreated biomass (41 %), it is low if the target is material applications (>80 %, with the lignin content being as low as possible), hence improved delignification is a target for further optimisation.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, there was a focus on cellulose dissolving ionic liquids, most prominently 1‐ethyl‐3‐methylimidazolium acetate, [EMIM][OAc] . More recently, a subclass of ionic liquids was discovered that has a high activity for separating cellulose and lignin but do not dissolve cellulose . This class of ionic liquids comprises inexpensive (∼$1.24/kg) and chemically stable ionic liquids containing hydrogen sulfate anions .…”
Section: Introductionmentioning
confidence: 99%
“…This IonoSolv ionic liquid is protic, acidic and effective in the presence of significant amounts of water. While the fractionation effect has been demonstrated in multiple conditions on a range of feedstocks (Chambon et al 2018(Chambon et al , 2019Gschwend et al 2019;Weigand et al 2017), and the lignin has been characterised in detail (Brandt et al 2015), the material properties of the resulting cellulose pulp remain to be determined. To fill this gap, we prepared a number of ionoSolv cellulose pulps from the energy crop Miscanthus 9 giganteus, a highyielding perennial grass that is a potential biorefinery feedstock, and analysed their polymer molar weight, material porosity, particle size and the cellulose crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…The reports exhibiting deconstruction along with saccharification follow a two-step protocol; at first, IL is used to separate lignin from cellulose, and then acids, alkalis, or enzymes are applied on the extracted delignified cellulose to yield sugars (Kassaye et al, 2017;Rocha et al, 2017;da Costa Lopes et al, 2018;Semerci and Guler, 2018). Some recent reports revealed the simultaneous removal of lignin and sugars from biomass using Brønsted acidic ILs but at high temperatures: 120-170 • C (Gschwend et al, 2012;Chambon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%